Integrated Assessment Framework for Practicum Science Mini Project Alamiah Models - Bakhtiar Ardiansyah; Agus Ramdani; Aliefman Hakim; Muh Makhrus (Journal of Educational Studies, 2026)
This study aims to provide an overview of the thinking framework in the assessment aspect that is implemented in an integrated manner in formative assessment in the application of the Alamiah mini project science practice model. This study is based on theoretical analysis related to formative assessment which is implemented to determine the achievement of the learning process implemented in the knowledge, skills and attitude specifications. The literature review is sourced from several articles in accredited journals Sinta and Scopus with the help of the publish and spreris application tool.The results of this study are in the form of a collection of assessment indicators implemented based on the Alamiah mini project science practice model which is currently being developed which can support the formative assessment process in an effort to fulfill student competencies in the knowledge aspect (high -level thinking skills), skills aspect (science process skills) and attitude (scientific attitude). The stages of learning in the Alamiah Mini Project Science practicum have equivalent indicators that can measure and inform student learning outcomes, especially at the Junior High School level.